Management Patterns of Extracurricular Arabic Language Learning in Higher Education Institutions in Pekanbaru - Nafisah Rahmah; Hakmi Wahyudi; Anugrah Ilahi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Arabic language programs in Indonesian higher education continue to face challenges related to student participation, opportunities for authentic practice, and the management of learning beyond formal classrooms. This study examines the management patterns of extracurricular Arabic language learning through student organizations and Arabic Language Week activities at Sultan Syarif Kasim State Islamic University of Riau and Riau Islamic University. The study used a qualitative field-research design and reports data from interviews, observations, field notes, and document review involving 18 participants from student organizations, supervising lecturers, and student participants. Data were analyzed through reduction, display, conclusion drawing, and verification, supported by triangulation and member checking. The findings show that the programs were managed through four interrelated stages: planning, organizing, implementation, and evaluation. Planning involved internal meetings and consultation with supervising lecturers; organization relied on task distribution and cross-divisional coordination; implementation emphasized participation, discipline, and collective responsibility; and evaluation was conducted after activities and through periodic review. Participants perceived Arabic Language Week as supporting conversation practice, vocabulary development, confidence, motivation, and the formation of an Arabic-speaking environment (bi’ah lughawiyyah). The findings indicate that institutional supervision and student-led management can provide a practical structure for extracurricular language learning. Because the study did not include direct proficiency measurement or longitudinal evidence, the reported learning benefits should be interpreted as participant perceptions rather than verified causal effects.